A nor-diterpene from Salvia sahendica leaves. Issue 15 (3rd August 2017) - Mofidi Tabatabaei, Sahar; Salehi, Peyman; Moridi Farimani, Mahdi; Neuburger, Markus; De Mieri, Maria; Hamburger, Matthias; Nejad-Ebrahimi, Samad
Abstract: Phytochemical investigation of n -hexane extract of Salvia sahendica by normal phase column chromatography resulted in the isolation of six compounds. Structures were established by 1D and 2D NMR spectroscopy, and HRMS, as a new norditerpene1, and known terpenoids, sclareol (2 ), oleanolic acid (3 ), β-sitosterol (4 ), salvigenin (5 ) and 3 α -hydroxy-11 α, 12 α -epoxyoleanan-28, 13 β -olide (6 ). The absolute configuration of1 was confirmed by a combination of X-ray single crystal analysis and electronic circular dichroism spectroscopy. In vitro cytotoxic activity on breast cancer cell line (MDA-MB-231) and also the antimicrobial activity of the pure compounds were tested against Staphylococcus aureus, Bacilus cereus and Escherichia coli . Abstract :